Powdered biosorbent from pecan pericarp (Carya illinoensis) as an efficient material to uptake methyl violet 2B from effluents in batch and column operations (2020)
The application of dyes in industrial processes has become a growing preoccupation due to the high quantities of colored effluents generated, which need previous treatment before being discarded in water bodies. A powdered biosorbent was then prepared from pecan pericarp and HCl, in order to treat colored effluents containing the dye methyl violet 2B (MV2B) using batch and fixed-bed operation modes. The new biosorbent, so-called powdered pecan pericarp (PPP), was characterized by functional groups related to cellulose, lignin, and hemicellulose. In addition, the material was composed of particles with different sizes, amorphous structure, and rugous surface. The best pH for MV2B biosorption on the PPP was 8.5. The kinetic profile was better described by the general order model, being the equilibrium rapidly reached in the first 5 min for different initial concentrations MV2B. The equilibrium curves were better described by the Langmuir model, indicating homogenous biosorption. The maximum biosorption capacity of 642 mg g−1 was reached at 328 K. Biosorption was favorable and endothermic. PPP has removed 94.1% of color in the simulated effluent. The fixed-bed assays revealed that the column packed with PPP could operate during 52.5 h with a height of 25 cm. The Thomas, Bohart-Adams, and Yoon-Nelson models were suitable to describe the dynamic curves. Therefore, PPP can be used as an efficient and fast biosorbent to treat textile effluents containing MV2B dye.